1997
DOI: 10.1002/(sici)1099-0488(199710)35:14<2293::aid-polb9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation transition of silk fibroin induced by blending chitosan

Abstract: The conformation of silk fibroin in silk fibroin/chitosan (SF/CS) blend membrane was analyzed by infrared spectrum, X‐ray diffractometry, and Raman spectrum. The results demonstrated that the SF could show β‐sheet conformation when the SF content in blend membranes was 10% (w/w) and 60–80% (w/w), while the pure SF membrane showed random coil conformation. A mechanism of the conformation transition was suggested in that the SF chain could use the rigid CS chain as a mold plate to stretch itself to form a β‐shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 2 publications
4
68
0
Order By: Relevance
“…According to the literature, when SF was mixed with other natural polymers containing hydroxyl groups (cellulose, alginate, heparin, and others), cross-linking between the polymers may benefit the conformational transition of SF [30]. Chen et al (1997) performed structural analyzes on SF and chitosan films [32]. Authors found that SF exhibited β-sheet structure, indicating that hydrogen bonding was formed between SF and chitosan in the blend films.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…According to the literature, when SF was mixed with other natural polymers containing hydroxyl groups (cellulose, alginate, heparin, and others), cross-linking between the polymers may benefit the conformational transition of SF [30]. Chen et al (1997) performed structural analyzes on SF and chitosan films [32]. Authors found that SF exhibited β-sheet structure, indicating that hydrogen bonding was formed between SF and chitosan in the blend films.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…The amount of drug unentrapped in the supernatant was calculated. The amount of drug entrapped was determined by subtracting amounts of free, uninterrupted drug from the total amount of ceftriaxone sodium taken [10][11][12].…”
Section: Entrapment Efficiency (Ee) Of Nanoparticlesmentioning
confidence: 99%
“…The first peak for chitosan at 898 cm -1 is assigned to the saccharide structure [16] . For the chitosan-PEO 100K blend IR spectra, the peak position is the same.…”
Section: Fourier Transform Infra Red (Ftir)mentioning
confidence: 99%